Sosialisasi Pemanfaatan Platfrom Quizizz sebagai Media Evaluasi Pembelajaran Matematika Berbasis Gamifikasi bagi Orang Tua - Silaban, Patri Janson; Ester Purba; Geby Sihombing; Kristin Sinaga; Gleadis Segala; Septiana Sitepu (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
An outreach activity regarding the use of the Quizizz platform—a gamification-based tool for mathematics learning assessment—was conducted to enhance parents' understanding and skills in utilizing digital technology to support their children's learning assessment processes at home. Preliminary observations revealed that most parents lacked familiarity with the Quizizz platform as an assessment tool. Some parents were even unaware of Quizizz's existence, relying instead on conventional methods and simple assessment techniques to assist their children's learning. This situation highlighted the need for education on digital technologies that can assist parents in supporting their children's learning. The activity aimed to equip parents with the understanding and skills to use Quizizz as an interactive, engaging, and gamification-based mathematics assessment tool. Held in Gang Pepaya, the activity involved two participating parents. The implementation utilized an interactive training approach comprising material presentation, a demonstration of the Quizizz platform, hands-on practice in creating mathematics quizzes, and a discussion and Q&A session. Through the practical component, participants had the opportunity to directly explore Quizizz features, thereby gaining the ability to create, access, and utilize quizzes for learning assessment. The results demonstrated an improvement in the parents' understanding and skills regarding the Quizizz platform; participants became capable of operating Quizizz and using assessment results to monitor their children's progress in mathematics. Furthermore, the parents responded positively, noting that Quizizz is user-friendly and capable of boosting children's engagement in learning activities. Thus, this outreach activity contributed positively to enhancing parents' digital skills, fostering a more interactive and enjoyable mathematics learning assessment process at home.